Angiotensin II Modulates Podocyte Glucose Transport - Lewko, Barbara; Maryn, Anna; Latawiec, Elzbieta; Daca, Agnieszka; Rybczynska, Apolonia (Frontiers in Endocrinology, 2018)
Podocytes, the cells playing a central role in maintaining a glomerular filtration barrier, are direct target for angiotensin II (AngII). Nonhemodynamic pathways of AngII signaling play a pivotal role in regulating cellular functions and mediating podocyte abnormalities in various glomerulopathies including diabetic kidney disease. In this study we investigated the ability of AngII to modulate glucose uptake into mouse podocytes expressing human AT1 receptor (AT1R+) after a 5-day exposition to normal (NG, 5.6 mmol/L) and to high (HG, 30 mmol/L) glucose. A short-(30 min) as well as a long-term (24 h) incubation with AngII markedly enhanced glucose transport in both NG and HG groups. In podocytes incubated in NG conditions , AngII inhibited insulin-stimulated glucose uptake. Regardless of the presence or absence of AngII, no effect of insulin on glucose uptake was observed in HG cells. Stimulation of glucose transport by AngII was mediated by protein kinase C (PKC) and by phosphoinositide 3-kinase (PI3-K). AngII modulated the expression of glucose transporters GLUT1, GLUT2 and GLUT4 on podocyte surface in a manner dependent on glucose concentration and time of exposure to AngII. Furthermore, despite its inhibitory effect on insulin action, AngII elevated the number of insulin receptors on podocyte surface in both NG and HG groups. Our findings indicate that AngII modulates basal, as well as insulin-dependent glucose uptake in podocytes by regulating the systems of glucose transporters and insulin signaling.